Graphite negative electrode material for lithium ion battery and preparation method of graphite negative electrode material
Through a new method of preparing graphite negative electrode material, high-pressure molding and sintering technology are used to enhance the bonding strength between particles, and residual carbon is removed through graphitization treatment, which solves the problem of weak structural strength of existing graphite negative electrode materials, significantly improving the storage performance and safety of the battery.
Patent Information
- Application Number
- CN202411855671.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The structural strength of existing graphite negative electrode materials is weak, which is difficult to withstand the electrochemical expansion stress during charging and discharging of lithium-ion batteries, resulting in damage to the material structure and affecting the storage performance and safety of the battery.
A new preparation method is adopted, including crushing the coke raw material and polymer to the micron level and physically mixing, and then continuously mixing with a liquid kneading agent under temperature controlled conditions to form a dense particle structure. Through high-pressure molding and sintering, the bonding strength between particles is further enhanced, and residual carbon is removed by graphitization to form a stable and densely structured graphite negative electrode material.
It significantly improves the structural density and particle strength of graphite negative electrode materials, reduces the damage to the material by electrochemical expansion stress, improves the storage performance and electrochemical stability of the battery, and enhances application safety.
Smart Images

Figure CN119660730A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy materials technology, specifically to a graphite anode material for lithium-ion batteries and its preparation method. Background Technology
[0002] Lithium-ion batteries are a type of rechargeable battery. Due to their high energy density, long lifespan, ability to undergo multiple charge-discharge cycles, and portability, they have become a hot research topic worldwide and are widely used in electric vehicles, energy storage base stations, and portable energy storage devices. Currently, commercially available lithium-ion batteries primarily use carbon materials, mainly graphite, as the anode material. However, the safety issues associated with commercially available graphite anode materials in power and digital products have remained unresolved and have been criticized by the market and domestic and international investors, making it difficult for related applications to be fully accepted by the end market. Therefore, developing graphite anode materials with better storage performance, stronger structural strength, better chemical stability, and higher safety during cycling is an urgent problem to be solved in lithium-ion rechargeable batteries.
[0003] The mainstream graphite products currently on the market are mainly produced by crushing coke into micronized particles, screening and classifying the micronized particles, mixing binders, and then performing secondary granulation using any of the vertical, horizontal, or continuous reactor methods before graphitization to obtain the corresponding graphite anode material products. The secondary granules of graphite anode materials manufactured using existing process assemblies often have a multi-particle secondary structure, resulting in insufficient bonding stress due to granulation technology issues. Generally, the bonding is mainly at particle points, with insufficient bonding across particle surfaces.
[0004] The main reason is that the existing secondary particle forming method for graphite anode materials involves mixing carbon-based raw material particles with asphalt-based polymer particles and granulating them using vertical, horizontal, or continuous reactors. This particle granulation technology mainly uses stirring and temperature control to soften, melt, and coke the asphalt-based polymer particles during the heating process, combined with low-speed stirring and movement, to complete the bonding of multiple particles.
[0005] This method cannot guarantee the compressive and shear forces between particles during granulation. The adhesion behavior of the particles is relatively random, and the adhesion is mostly point-to-point or point-to-surface bonding between particles. The strength of such secondary graphite particle bonding structures is relatively weak and easily damaged by external and internal stresses. At the same time, due to insufficient shear and compressive forces applied by the equipment during particle granulation and bonding, the resulting secondary particle structure not only has weak structural strength but also contains many voids.
[0006] Therefore, it is important to clarify that carbon-based raw material particles are irregular geometric shapes with numerous sharp angles on their surfaces, all of which affect the structural stability of the graphite anode material bonding. This is mainly manifested in the destruction of the graphite particle structure during the rolling process in lithium battery manufacturing and in the cyclic lithium insertion / extraction process. Due to the repeated expansion of the graphite anode material particles coated on the current collector copper foil, the original bonding structure of the graphite anode material is easily damaged, leading to a rapid loss of material structural strength. The damaged graphite anode particles will generate new graphite end faces, which will react violently with the electrolyte, consuming lithium ions and electrolyte components to repair and form the SEI film. This consumes a large amount of electrolyte and lithium ions, intensifying the internal reaction activity of the battery pack and reducing storage performance and safety performance. It is also important to clarify that the total amount of various BOM materials in each battery pack is relatively fixed. Therefore, the accelerated consumption of any one or several battery BOM materials will become a bottleneck in the battery's calendar life, creating a bottleneck effect.
[0007] More seriously, lithium-ion batteries are prone to pulverization and detachment during charging and discharging, causing violent reactions inside the battery pack during charging and discharging, resulting in gas generation, lithium dendrite formation, and safety issues caused by thermal runaway of the battery pack.
[0008] It is evident that the existing graphite anode preparation process and methods produce secondary granular graphite materials with relatively weak structural strength, which are difficult to withstand the damage to the material structure caused by expansion stress during battery charging and discharging, thus affecting the overall storage safety of the battery pack in application.
[0009] Therefore, it is indeed necessary to develop a high-storage-performance graphite anode material for lithium-ion batteries to obtain a graphite anode material for lithium-ion batteries with good storage performance and safety, thereby overcoming the technical difficulties in this field. Summary of the Invention
[0010] The technical problem to be solved by the present invention is to overcome the defects of the above-mentioned technology and provide a graphite anode material for lithium-ion batteries and its preparation method.
[0011] To solve the above-mentioned technical problems, the present invention provides a method for preparing graphite anode material for lithium-ion batteries, comprising the following steps:
[0012] S1) The coke raw material and the polymer are pulverized to the micron level and then physically mixed and homogenized to obtain a mixture;
[0013] S2) The mixture is continuously kneaded with room temperature liquid kneading agent under temperature control to obtain kneaded raw material;
[0014] S3) The mixed raw materials are filled into the continuous molding trough module and pressure is applied to complete the molding of the preform and obtain the preformed initial preform;
[0015] S4) The pre-made initial blank is sintered in an inert gas continuous furnace to obtain a sintered blank;
[0016] S5) The sintered preform is crushed, graded and screened, surface oxidized, graphitized and processed to obtain graphite anode material.
[0017] Furthermore, in step S1, the coke raw material is selected from one or more types of oil-based non-needle raw coke, oil-based non-needle calcined coke, etc., and its micron-sized powder particle size D50 is 0.1-20μm;
[0018] The polymer is selected from one or more combinations of coal-based pitch, oil-based pitch, phenolic resin, etc., and its micron-sized powder particle size D50 is 0.1-20μm; the polymer is one or more combinations of coal-based pitch, oil-based pitch, phenolic resin, and its micron-sized powder particle size D50 is 0.1-20μm.
[0019] Furthermore, in step S1, when the coke raw material and the micron-sized powder of the polymer are mixed and homogenized, the mass ratio of the two is 95:5 to 70:30, and the mixing and homogenization stirring speed is 19 to 79 rpm.
[0020] Furthermore, in step S2, the room-temperature liquid kneading agent is one or more combinations of heavy oil, room-temperature liquid coal-based pitch, and room-temperature liquid oil-based pitch.
[0021] The ratio of the mixture to the room-temperature liquid kneading agent is 92:8 to 75:25, the temperature is controlled at 80-220℃, and the speed of the kneading agitator is 20-65 rpm.
[0022] Furthermore, the initial molding pressure of the embryo in step S3 is 20-150 MPa.
[0023] Furthermore, the sintering temperature of the preform in step S4 is controlled at 500-1100℃;
[0024] The inert gas is one or a mixture of nitrogen, argon, and oxygen, and the gas injection velocity into the furnace is 17-310 m / s. 3 / h, the embryo propulsion linear velocity is 1-10m / h.
[0025] Furthermore, in step S5, the particle size D50 of the crushed embryo is controlled within 3-24 μm, and air is used to oxidize the surface of the crushed embryo particles, with the air injection flow rate controlled within 6-28 m³ / h. 3 The material turning drum speed is 5-15 rpm, the graphitization temperature is controlled at 2600-3000℃, and the resulting graphite anode material is in powder form with a particle size D50 of 1.0~22.0μm.
[0026] A second objective of this invention is to provide a graphite anode material for lithium-ion batteries prepared by the above-described method.
[0027] The advantages of this invention compared to existing technologies are as follows: The preparation method of the graphite anode material for lithium-ion batteries provided by this invention differs from the existing graphite particle granulation technology for graphite anode materials. The graphite anode material prepared by the method described above has the advantages of dense structure, high particle strength, few end faces on the particle surface, and good stability. It can significantly improve the destruction of the particle structure of graphite anode materials caused by electrochemical expansion stress during the charging and discharging process of lithium-ion batteries, reduce the residual carbon coverage area on the surface of the graphite anode material, thereby reducing the coverage area of the end faces with strong reactivity on the particle surface, and significantly improve the storage performance, electrochemical stability, and application safety of the material. Attached Figure Description
[0028] Figure 1 This is a preform diagram of a graphite anode material for lithium-ion batteries and its preparation method according to the present invention.
[0029] Figure 2 This is a SEM image of a graphite anode material for lithium-ion batteries and its preparation method, as described in this invention.
[0030] Figure 3 This is a transmission electron microscope (SEM) image of the cross-sectional area of the graphite anode material obtained in an embodiment of the present invention, which describes a graphite anode material for lithium-ion batteries and its preparation method.
[0031] Figure 4 This is a comparative example of a graphite anode material for lithium-ion batteries and its preparation method, obtained by transmission electron microscopy (SEM) of the particle cross-section of the graphite anode material. Detailed Implementation
[0032] The following detailed description, in conjunction with embodiments, illustrates a graphite anode material for lithium-ion batteries and its preparation method according to the present invention.
[0033] Example 1
[0034] A method for preparing a graphite anode material for lithium-ion batteries includes the following steps:
[0035] S1: Mix and homogenize oil-based needle coke B0 with a median particle size (D50) of 6.0-8.0μm and oil-based asphalt powder with a softening point of 150±3℃ and a median particle size (D50) of 6-8μm at a mass ratio of 88:12. The mixing speed is 30rpm and the mixing time is 40min to obtain the mixture.
[0036] S2: Mix the mixture prepared in S1 with heavy oil H0 in a mass ratio of 87:13, knead at a kneading temperature of 120℃, a heating rate of 10℃ / min, hold at a constant temperature for 30min, and a kneading paddle speed of 46rpm to obtain the kneaded raw material.
[0037] S3: Put the mixed raw materials into the cylindrical molding module trough, with a filler amount of 10-20kg, a maximum pressure of 85MPa, and a holding time of 50s to obtain the initial preform;
[0038] S4: The initial preform prepared in S3 is sintered at 800℃ with a preform feed rate of 8 m / s, a heating rate of 3℃ / min before isothermal treatment, and held at 800℃ for 2.5 h. The nitrogen flow rate in the furnace is 40 m³ / min. 3 / h, to obtain a sintered green body;
[0039] S5: The sintered preform prepared in S4 is crushed and screened to obtain a precursor with a medium particle size D50 of 13-15 μm. The precursor is then subjected to surface oxidation in a continuous drum furnace to remove residual carbon from the particle surface, with the air injection flow rate controlled at 12 m³ / h. 3 The material turning drum rotates at 8 rpm per hour; then, an Atchison graphitization furnace is used for graphitization at a temperature of 2850-2900℃. The graphitized material is then screened to obtain the high-storage-performance graphite anode material of Example 1.
[0040] Example 2
[0041] A method for preparing a graphite anode material for lithium-ion batteries includes the following steps:
[0042] S1: Mix and homogenize coal-based needle coke B1 with a median particle size (D50) of 8.0-10.0μm and oil-based asphalt powder P0 with a median particle size (D50) of 6-8μm and a softening point of 150±3℃ at a mass ratio of 90:10. The mixing speed is 30rpm and the mixing time is 40min to obtain the mixture.
[0043] S2: Mix the mixture prepared in S1 with heavy oil H0 in a mass ratio of 87:13, knead at a kneading temperature of 120℃, a heating rate of 10℃ / min, hold at a constant temperature for 30min, and a kneading paddle speed of 46rpm to obtain the kneaded raw material.
[0044] S3: Put the mixed raw materials into the cylindrical molding module trough, with a filler amount of 10-20kg, a maximum pressure of 85MPa, and a holding time of 50s to obtain the initial preform;
[0045] S4: The initial green body prepared in S3 is sintered at 800℃ with a green body feed rate of 8m / s, a heating rate of 3℃ / min before isothermal treatment, and isothermal treatment at 800℃ for 2.5h. The nitrogen flow rate in the furnace is 40m³ / min. 3 / h, to obtain a sintered green body;
[0046] S5: The sintered preform prepared in S4 is crushed and screened to obtain a precursor with a medium particle size D50 of 13-15 μm; the precursor is then subjected to surface oxidation in a continuous drum furnace to remove residual carbon from the particle surface, with the air injection flow rate controlled at 12 m³ / h. 3 The material turning drum rotates at 8 rpm per hour; then, an Atchison graphitization furnace is used for graphitization at a temperature of 2850-2900℃. The graphitized material is then screened to obtain the high-storage-performance graphite anode material of Example 2.
[0047] Example 3
[0048] A method for preparing a graphite anode material for lithium-ion batteries includes the following steps:
[0049] S1: Oil-based needle coke B0 with a median particle size (D50) of 10.0-12.0μm and coal-based pitch powder with a median particle size (D50) of 6-8μm and a softening point of 150±3℃ P1 are mixed and homogenized at a mass ratio of 92:8. The mixing speed is 30rpm and the mixing time is 40min to obtain the mixture.
[0050] S2: Mix the mixture prepared in S1 with heavy oil H0 at a mass ratio of 85:15, knead at a kneading temperature of 120℃, a heating rate of 10℃ / min, a constant temperature of 30min, and a kneading paddle speed of 46rpm to obtain the kneaded raw material.
[0051] S3: Put the mixed raw materials into the cylindrical molding module trough, with a filler amount of 10-20kg, a maximum pressure of 85MPa, and a holding time of 50s to obtain the initial preform;
[0052] S4: The initial green body prepared in S3 is sintered at 800℃ with a green body feed rate of 8m / s, a heating rate of 3℃ / min before isothermal treatment, and isothermal treatment at 800℃ for 2.5h. The nitrogen flow rate in the furnace is 40m³ / min. 3 / h, to obtain a sintered green body;
[0053] S5: The sintered preform prepared in S4 is crushed and screened to obtain a precursor with a medium particle size D50 of 13-15 μm; the precursor is then subjected to surface oxidation in a continuous drum furnace to remove residual carbon from the particle surface, with the air injection flow rate controlled at 12 m³ / h. 3 The material turning drum rotates at 8 rpm per hour; then, an Atchison graphitization furnace is used for graphitization at a temperature of 2850-2900℃. The graphitized material is then screened to obtain the high-storage-performance graphite anode material of Example 3.
[0054] Example 4
[0055] A method for preparing a graphite anode material for lithium-ion batteries includes the following steps:
[0056] S1: Mix and homogenize oil-based needle coke B0 with a median particle size (D50) of 8.0-10.0μm and oil-based asphalt powder with a softening point of 150±3℃ and a median particle size (D50) of 8-10μm at a mass ratio of 88:12. The mixing speed is 30rpm and the mixing time is 40min to obtain the mixture.
[0057] S2: Mix the mixture prepared by S1 with liquid oil-based asphalt Y0 at a mass ratio of 84:16, knead at a kneading temperature of 120℃, a heating rate of 10℃ / min, a constant temperature of 30min, and a kneading paddle speed of 46rpm to obtain the kneaded raw material.
[0058] S3: Put the mixed raw materials into the cylindrical molding module trough, with a filler amount of 10-20kg, a maximum pressure of 85MPa, and a holding time of 50s to obtain the initial preform;
[0059] S4: The initial preform prepared in S3 is sintered at 800℃ with a preform feed rate of 8 m / s, a heating rate of 3℃ / min before isothermal treatment, and held at 800℃ for 2.5 h. The nitrogen flow rate in the furnace is 40 m³ / min. 3 / h, to obtain a sintered green body;
[0060] S5: The sintered preform prepared in S4 is crushed and screened to obtain a precursor with a medium particle size D50 of 13-15 μm; the precursor is then subjected to surface oxidation in a continuous drum furnace to remove residual carbon from the particle surface, with the air injection flow rate controlled at 12 m³ / h. 3 The material turning drum rotates at 8 rpm per hour; then, an Atchison graphitization furnace is used for graphitization at a temperature of 2850-2900℃. The graphitized material is then screened to obtain the high-storage-performance graphite anode material of Example 4.
[0061] Comparative Example 1
[0062] The method for preparing the lithium-ion battery graphite anode material provided in Comparative Example 1 includes the following steps:
[0063] 1-1) Preferably, use oil-based needle coke B0, crushed to a medium particle size D50 of 6-8 μm. Preferably, use oil-based asphalt with a softening point of 150±3℃, pulverized to a medium particle size of 6-8 micrometers, and mixed and homogenized according to a mass ratio of 88:12, with a mixing speed of 30 rpm and a mixing time of 40 min to obtain the mixture.
[0064] 1-2): The mixture prepared in 1-1 is granulated in a horizontal reactor. The granulation temperature is controlled at 600℃ for 2 hours. The heating rate before the constant temperature is 10℃ / min. The stirring speed of the horizontal reactor is 28 rpm to obtain granulated material.
[0065] 1-3) The granulated material prepared in 1-2 is crushed and screened, and the medium particle size D50 is controlled at 13-15μm to obtain crushed granulated material;
[0066] 1-4) The crushed and granulated material prepared in 1-3 is sintered. The material feed linear velocity is 8 m / s, the heating rate before isothermalization is 3℃ / min, and the temperature is maintained at 800℃ for 2.5 h. The nitrogen flow rate in the furnace is 40 m³ / min. 3 / h, to obtain sintered precursors of 13-15μm;
[0067] 1-5) The 13-15μm sintering precursor prepared in 1-4 was graphitized in an Atchison graphitization furnace at a temperature of 2850-2900℃. The graphitized material was then screened to obtain the graphite anode material of Comparative Example 1.
[0068] Comparative Example 2
[0069] The method for preparing the lithium-ion battery graphite anode material provided in Comparative Example 2 includes the following steps:
[0070] 1-1) Preferred coal-based needle coke B1 is crushed to a medium particle size D50 of 8-10 μm. Preferred oil-based asphalt with a softening point of 150±3℃ is pulverized P1, with a medium particle size controlled at 6-8 micrometers. The mixture is homogenized and mixed according to a mass ratio of 90:10, with a mixing speed of 30 rpm and a mixing time of 40 min to obtain the mixture.
[0071] 1-2) The mixture prepared in 1-1 was granulated in a horizontal reactor. The granulation temperature was controlled at 600℃ for 2 hours. The heating rate before the constant temperature was 10℃ / min. The stirring speed of the horizontal reactor was 28 rpm to obtain the granulated material.
[0072] 1-3) The granulated material prepared in 1-2 is crushed and screened, and the medium particle size D50 is controlled at 13-15μm to obtain crushed granulated material;
[0073] 1-4) The crushed and granulated material prepared in 1-3 is sintered. The material feed linear velocity is 8 m / s, the heating rate before isothermalization is 3℃ / min, and the temperature is maintained at 800℃ for 2.5 h. The nitrogen flow rate in the furnace is 40 m³ / min. 3 / h, to obtain sintered precursors of 13-15μm;
[0074] 1-5) The 13-15μm sintering precursor prepared in 1-4 was graphitized in an Atchison graphitization furnace at a temperature of 2850-2900℃. The graphitized material was then screened to obtain the graphite anode material of Comparative Example 2.
[0075] Comparative Example 3
[0076] The method for preparing the lithium-ion battery graphite anode material provided in Comparative Example 3 includes the following steps:
[0077] 1-1) Preferably, use oil-based needle coke B1, crushed to a medium particle size D50 of 10-12 μm. Preferably, use oil-based asphalt powder P1 with a softening point of 150±3℃, with a medium particle size controlled at 6-8 micrometers. Mix and homogenize the powder according to a mass ratio of 90:10, with a mixing speed of 30 rpm and a mixing time of 40 min to obtain the mixture.
[0078] 1-2) The mixture prepared in 1-1 is granulated in a vertical reactor. The granulation temperature is controlled at 600℃ for 2 hours. The heating rate before the constant temperature is 10℃ / min. The stirring speed of the horizontal reactor is 28 rpm to obtain the granulated material.
[0079] 1-3) The granulated material prepared in 1-2 is crushed and screened, and the medium particle size D50 is controlled at 13-15μm to obtain crushed granulated material.
[0080] 1-4) The crushed and granulated material prepared in 1-3 is sintered. The material feed linear velocity is 8 m / s, the heating rate before isothermalization is 3℃ / min, and the temperature is maintained at 800℃ for 2.5 h. The nitrogen flow rate in the furnace is 40 m³ / min. 3 / h, to obtain sintered precursors of 13-15μm;
[0081] 1-5) The 13-15μm sintering precursor prepared in 1-4 was graphitized in an Atchison graphitization furnace at a temperature of 2850-2900℃. The graphitized material was then screened to obtain the graphite anode material of Comparative Example 3.
[0082] Example 5
[0083] Furthermore, the finished products obtained in Examples 1-4 and Comparative Examples 1-3 were used to measure relevant parameters, as follows:
[0084] Test 1) The particle size range and distribution of the material were tested using a Malvern MS3000 laser particle size analyzer.
[0085] Test 2) The specific surface area of the material was tested using the Tristar3000 fully automated specific surface area and porosity analyzer from Micron Instruments, Inc.
[0086] Test 3) The morphology and particle size of the samples were observed using a Hitachi S4800 scanning electron microscope.
[0087] Test 4) The extrusion and shear tests were conducted on the structural strength of the finished particles using the grinding method. A certain amount of graphite negative electrode finished powder was placed on the surface of the grinding disc. After grinding with fixed parameters, the particle size of the finished powder was compared before and after grinding to observe the trend of particle size change.
[0088] Calculation of particle structure breakage rate: (D50 before grinding - D50 after grinding) / D50 before grinding × 100% is the particle strength characterization value. The smaller the value, the stronger the material structure strength.
[0089] Test 5) The storage performance of graphite anode material was tested under the condition of 30 days@60℃ using a 1.5Ah soft-pack battery cell.
[0090] The conclusions of tests 1 through 5 were statistically analyzed and presented in Table 1:
[0091] Table 1 Summary of Measurement Results for Tests 1-5
[0092]
[0093] Test 6) The ordered and disordered layers of the graphite profile were monitored using a Hitachi H-9500 transmission electron microscope.
[0094] Monitoring has shown that, for example Figure 3 The edges of the graphite anode material particles obtained in Examples 1-4 are found to be all ordered graphite layers. The ordered graphite layers do not require the consumption of electrolyte to form an SEI film with lithium ions, and the interface exhibits strong stability during charging and discharging.
[0095] like Figure 4 As shown, disordered graphite layers enriched at the edge of the graphite anode material particle profile (i.e., particle surface) obtained in Comparative Examples 1-3 were found. The disordered graphite layers are not conducive to the formation of a stable SEI film, and the interface exhibits strong reactivity during charging and discharging.
[0096] The working principle of this invention is as follows: The preparation method provided by this invention mainly involves high-pressure extrusion of carbon-based raw material particles with solid-liquid binders and kneading agents. This allows the micron-sized carbon-based raw material particles to be compressed and bonded to the maximum extent under high pressure. Simultaneously, the softening and increased fluidity of the solid binder after heating, combined with the liquid kneading agent, completes the densification and shaping of the carbon-based raw material particles during the high-pressure extrusion process. This ensures that the carbon-based raw material particles are maximally bonded under the extrusion pressure, while the softened solid binder and the kneading agent, with their good fluidity, further strengthen the inter-particle bonding structure and fill the tiny gaps between particles. Subsequently, sintering causes the binder and kneading agent to semi-carbonize, further strengthening the inter-particle bonding strength. Finally, micron-sized particles are broken down to the size of graphite anode material products.
[0097] Simultaneously, during the crushing process, weakly bonded particle connection points and surfaces can be pre-separated, ensuring that the secondary particles after crushing are all strongly bonded structures. Surface oxidation of the secondary particle structure removes residual carbon that is difficult to graphitize and highly reactive due to sintering of binders and kneading agents. After graphitization, a dense graphite anode material with high particle strength, few particle surface ends, and good stability is obtained.
[0098] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention; the actual structure is not limited thereto. In conclusion, if those skilled in the art are inspired by this description and design similar structures and embodiments without departing from the spirit of the invention, such designs should fall within the protection scope of the present invention.
Claims
1. A method for preparing a graphite negative electrode material for a lithium ion battery, characterized in that: The following steps are involved: S1) crushing the coke raw material and the high molecular polymer into micrometer level respectively and physically mixing and homogenizing them to obtain a mixture; S2) continuously kneading the mixed material with a room temperature liquid kneading agent under temperature control conditions to obtain a kneading raw material; S3) filling the kneaded raw materials into a continuous pressing trough module and applying pressure to complete embryo body pressing to obtain a prefabricated initial embryo body; S4) sintering the prefabricated initial embryonic body in an inert gas continuous furnace to obtain a sintered embryonic body; S5) The sintered green body is processed through crushing, grading and screening, surface oxidation, graphitization and finished product processing to obtain a graphite negative electrode material.
2. The preparation method according to claim 1, characterized in that: In the step S1, the coke raw material is selected from one or more combinations of various types such as oil-based non-needle green coke, oil-based non-needle calcined coke, etc., and its micron-level powder particle size D50 is 0.1-20μm; the high molecular polymer is selected from one or more combinations of coal-based asphalt, oil-based asphalt, phenolic resin, etc., and its micron-level powder particle size D50 is 0.1-20μm; the high molecular polymer is one or more combinations of coal-based asphalt, oil-based asphalt, phenolic resin, etc., and its micron-level powder particle size D50 is 0.1-20μm.
3. The preparation method according to claim 1, characterized in that: In the step S1, when the coke raw material and the micron-sized powder of the high molecular polymer are mixed and homogenized, the mass ratio of the two is 95:5 to 70:30, and the mixing and homogenizing stirring speed is 19 to 79 rpm.
4. The preparation method according to claim 1, characterized in that: In step S2, the room temperature liquid kneading agent is one or more combinations of heavy oil, room temperature liquid coal-based asphalt, and room temperature liquid oil-based asphalt; the ratio of the mixture to the room temperature liquid kneading agent is 92:8 to 75:25, the temperature is controlled at 80-220°C, and the speed of the kneading stirring paddle is 20-65rpm.
5. The preparation method according to claim 1, characterized in that: The initial embryo molding pressure in step S3 is 20-150 MPa.
6. The preparation method according to claim 1, characterized in that: In step S4, the sintering temperature of the prefabricated body is controlled to be 500-1100°C; the inert gas is a mixture of one or more of nitrogen, argon and oxygen, and the gas injection rate into the furnace is 17-310m / s. 3 / h, the embryo advancement linear speed is 1-10m / h.
7. The preparation method according to claim 1, characterized in that: In step S5, the particle size D50 of the embryo body crushed is controlled to be 3-24 μm, the surface oxidation atmosphere of the embryo body crushed particles is air, and the air injection flow rate is controlled to be 6-28 m 3 / h, the material turning drum speed is 5-15rpm, the graphitization temperature is controlled at 2600-3000℃, and the obtained graphite negative electrode material is in powder form with a particle size D50 of 1.0-22.0μm.
8. A graphite negative electrode material for a lithium ion battery obtained by the preparation method according to any one of claims 1 to 7.